Review on Odor Localization - Nyayu Latifah Husni; Siti Nurmaini; Irsyadi Yani (IAES Indonesia Section, 2015)
In this paper, the importance of odor localization isexplained. The researchers that investigated the experimentsand applications of odor localization using static sensors, mobilesensors (that were integrated in single robot, multi robot, andswarm robot) are described. However, there are some difficultiesfaced by the researchers in applying the mobile robots in the realsituation, such as: the speed of mobile robots are not as fast asthe odor patches transporting and the use of more than onesensor in mobile robot can make noises or errors. In the future,the plume finding in the uncertain environment and thechallenges mentioned above will be the authors’ consideration.